Content Analysis of Social Media Posts and Their Role in Supporting Knowledge Management Processes in the Saudi Ministry of Education - Aljehani, Rawan Khaled; Almoqati, Rahaf Mohammed (Arab Journal for Sciences and Research Publishing, 2025)
This study aimed to examine the role of the Ministry of Education’s social networks in supporting knowledge management processes by employing a mixed analytical approach that integrated qualitative and quantitative techniques. Advanced tools were utilized, including MAXQDA for network and content analysis, Brand24 for digital sentiment analysis, and Tw Extract for generating a precise quantitative sample of tweets. The study population consisted of the Ministry’s posts on the X platform, while the sample included 200 tweets published between 2020 and 2025, in addition to sentiment data related to the hashtag #الوظائف_التعليمية during 16–25 April 2025. The analysis focused on the four core knowledge management processes: knowledge creation, organization, sharing, and application. Results showed varying levels of implementation, with knowledge sharing scoring 93%, followed by knowledge creation at 86%, knowledge application at 86%, and knowledge organization at 80%. Sentiment analysis indicated predominantly neutral reactions (67%), compared to 23% positive and 10% negative sentiments. These findings highlight the Ministry’s strong informational presence contrasted with limited interactive and participatory knowledge practices. The study recommends enhancing mechanisms for capturing user-driven knowledge, developing participatory tools to improve application effectiveness, and integrating sentiment analysis into decision-making to strengthen the Ministry’s digital knowledge ecosystem and foster more interactive and comprehensive knowledge processes across its platforms.